Bhuda Cemeng Klawu dan Pemujaan Dewi Kekayaan Perspektif Teologi Hindu - Acyutananda Wayan Gaduh (Sphatika: Jurnal Teologi, 2023)
Hindu theology provides the broadest way to worship God. One of them is the celebration of Bhuda Cemeng Klawu which is a holy day for the Balinese Hindu community to worship the manifestation of God as the ruler of prosperity, especially financial wealth. Based on the observations, on this day, Hindus perform worship rituals to Bhatari Rambut Sedhana by offering some banten. Bhatari Rambut Sadhana is embodied in 2 statues made of kepeng coins as a symbol of beauty and splendor. Worship on Buddha Cemeng Klawu day should be carried out by all Hindus, not only traders and business people. Prosperity is coveted by everyone, and wealth has a significant role in our life. In the Hinduism religion, wealth is not taboo. Everyone is encouraged to be rich, especially those who are in the gṛhasta period. Wealth (arta) is one of the goals of Hinduism in Catur Purusa Artha. Wealth enables one to perform charity (punia) as one of the yajña to realize Jagadhita. on the other hand, wealth very easy to make people drunk and complacent. The Budha Cemeng Klawu celebration reminds Hindus to always be grateful for the wealth they have and seek and use wealth for good. Hopefully, this article can open a wider understanding for Hindus regarding the meaning of holy days, especially Budha Cemeng Klawu.